MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI TEKS BERITA KELAS XI.B2 SMA NEGERI 7 PALEMBANG - Syafira Wulandari; Yunike Maulia; Meliyani Meliyani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the world of education, of course there is a need for learning motivation for students in order to achieve success in learning. The learning process can be said to be successful if the learning environment is comfortable and safe and learning is in favor of students according to the times in accordance with 21st century education. This research aims to determine the application of the Jigsaw Type cooperative learning model to increase students' learning motivation in News Text material for class XI.B2 SMA Negeri 7 Palembang. The method used is a mixed method of qualitative and quantitative. The results found in this research were in the form of the use of the jigsaw type cooperative learning model, there was an increase in student learning outcomes seen from the students' grades in each cycle. The average score in Cycle I was 67.4 with a percentage of 65% and in Cycle II the average score of students increased to 81 with a percentage of 90%. This means that the use of the previous learning model is not appropriate, so you have to replace the latest learning model which is more creative and innovative, such as the jigsaw type cooperative learning model.